Custom software installation and availability assurance of computing elements in LHC Grid - Karen Mkoyan (Изд-во НАН РА)
This paper describes the process of custom software installation and validation in the LHC Grid. It also provides set of scripts developed by author for availability assurance and overall monitoring of computing elements prior to installation, and a script for the installation and validation process itself.
Keywords: Mathematics; Computer software